2006
DOI: 10.1038/modpathol.3800476
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of Skp2, c-Myc and p27 proteins but not mRNA after H. pylori eradication in chronic gastritis

Abstract: Helicobacter pylori infection is associated with increased gastric epithelial cell turnover and non-cardia gastric cancer. Cell cycle progression is dependent on the proteasomal degradation of p27, a cyclin-dependent kinase inhibitor and gastric tumor suppressor, following ubiquitination mediated by Skp2. c-Myc is a transcriptional repressor of p27 and also a target of Skp2. In vitro, H. pylori decreases p27 protein post-translationally. We aimed to determine how p27 is regulated by H. pylori in vivo. The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 47 publications
3
30
0
Order By: Relevance
“…Transfection of p27 kip1 into cell lines increased susceptibility to H. pylori induced apoptosis [37], while H. pylori infection of p27 kip1 knockout mice led to increased rates of dysplasia and gastric cancer at 75 weeks postinfection [38 ]. These findings are also being translated into the clinical arena as p27 kip1 protein expression is increased in human gastric antrum following H. pylori eradication [39]. The gastric mucosal growth factor Reg is another important factor in gastric carcinogenesis.…”
Section: Host Factorsmentioning
confidence: 94%
“…Transfection of p27 kip1 into cell lines increased susceptibility to H. pylori induced apoptosis [37], while H. pylori infection of p27 kip1 knockout mice led to increased rates of dysplasia and gastric cancer at 75 weeks postinfection [38 ]. These findings are also being translated into the clinical arena as p27 kip1 protein expression is increased in human gastric antrum following H. pylori eradication [39]. The gastric mucosal growth factor Reg is another important factor in gastric carcinogenesis.…”
Section: Host Factorsmentioning
confidence: 94%
“…These cytokines recruit neutrophils and macrophages to sites of inflammation, but prolonged exposure to these cytokines has been linked clinically to increased gastric cancer risk (58)(59)(60)(61)(62)(63). H. pylori infection has been associated with increased IL-8 expression and decreased p27 levels (64). Both reduced p27 levels and increased IL-8 levels have been shown to mediate decreased apoptosis (65)(66)(67)(68).…”
Section: Origin Alters Transcription and Virulence Of H Pylorimentioning
confidence: 99%
“…Kim et al [65] investigated the expression of MYC protein and mRNA in 22 patients with chronic gastritis who had been successfully treated for H pylori. Two endoscopic antral biopsies were taken before and 2 mo after H pylori eradication.…”
Section: Myc and Gastric Carcinogenesismentioning
confidence: 99%
“…These authors found that MYC expression was significantly higher in those lesions of type Ⅲ intestinal metaplasia and dysplasia Ⅱ-Ⅲ with cagA than in those without cagA. Nardone et al [64] also suggested that the increased prevalence of MYC expression was in agreement with the high prevalence of cagA positivity seen in the population studied.Kim et al [65] investigated the expression of MYC protein and mRNA in 22 patients with chronic gastritis who had been successfully treated for H pylori. Two endoscopic antral biopsies were taken before and 2 mo after H pylori eradication.…”
mentioning
confidence: 99%